3D Bridged Carbon Nanoring/Graphene Hybrid Paper as a High‐Performance Lateral Heat Spreader. Issue 46 (13th October 2015) - Zhang, Jianwei; Shi, Gang; Jiang, Cai; Ju, Su; Jiang, Dazhi
Abstract : Graphene paper (GP) has attracted great attention as a heat dissipation material due to its unique thermal transfer property exceeding the limit of graphite. However, the relatively poor thermal transfer properties in the normal direction of GP restricts its wider applications in thermal management. In this work, a 3D bridged carbon nanoring (CNR)/graphene hybrid paper is constructed by the intercalation of polymer carbon source and metal catalyst particles, and the subsequent in situ growth of CNRs in the confined intergallery spaces between graphene sheets through thermal annealing. Further investigation demonstrates that the CNRs are covalently bonded to the graphene sheets and highly improve the thermal transport in the normal direction of the CNR/graphene hybrid paper. This full‐carbon architecture shows excellent heat dissipation ability and is much more efficient in removing hot spots than the reduced GP without CNR bridges. This highly thermally conductive CNR/graphene hybrid paper can be easily integrated into next generation commercial high‐power electronics and stretchable/foldable devices as high‐performance lateral heat spreader materials. This full‐carbon architecture also has a great potential in acting as electrodes in supercapacitors or hydrogen storage devices due to the high surface area. Abstract : 3D bridged carbon nanoring (CNR)/graphene hybrid paper is fabricated with a novel approach. In situ growth of CNRs is achieved by the intercalation of polymer carbon source and metal catalyst in the confined space between graphene sheets. The CNRs highly improve thermal transport in the normal direction of the hybrid paper, generating an excellent lateral heat spreader.